Insight into metal immobilization and microbial community structure in soil from a steel disposal dump phytostabilized with composted, pyrolyzed or gasified wastes. (June 2021) - Radziemska, Maja; Gusiatin, Zygmunt M.; Cydzik-Kwiatkowska, Agnieszka; Cerdà, Artemi; Pecina, Vaclav; Bęś, Agnieszka; Datta, Rahul; Majewski, Grzegorz; Mazur, Zbigniew; Dzięcioł, Justyna; Danish, Subhan; Brtnický, Martin
Abstract: The soil system is a key component of the environment that can serve as a sink of pollutants. Using processed waste for aided phytostabilization of metals (HMs) in contaminated soils is an attractive phytoremediation technique that integrates waste utilization and recycling. In this study, we evaluated the effect of biologically and thermally processed wastes, i.e. sewage sludge compost (CSS), poultry feather ash (AGF) and willow chip biochar (BWC), on phytostabilization of contaminated soil from a steel disposal dump. Greenhouse experiments with Lupinus luteus L. and amendments (dosage: 3.0%, w/w) were conducted for 58 days. Soil toxicity was evaluated with Ostracodtoxkit and Phytotoxkit tests. At the end of the experiment, soil pH, plant biomass yield, and HM accumulation in plant tissues were determined. HM distribution, HM stability (reduced partition index) and potential environmental risk (mRI index) in the soil were assessed. During phytostabilization, changes in the diversity of the rhizospheric bacterial community were monitored. All amendments significantly increased soil pH and biomass yield and decreased soil phytotoxicity. AGF and BWC increased accumulation of individual HMs by L. luteus roots better than CSS (Cu and Cr, and Ni and Zn, respectively). The soil amendments did not improve Pb accumulation by the roots. Improvements in HM stability depended on amendment type: Ni and Pb stability were improved by all amendments; Zn stability, by AGF, and BWC; Cd stability, by AGF; and Cr stability, by BWC. AGF reduced the mRI most effectively. Microbial diversity in amended soils increased with time of phytostabilization and was up to 9% higher in CSS amended soil than in control soil. AGF application favored the abundance of the genera Arenimonas, Brevundimonas, Gemmatimonas and Variovorax, whose metabolic potential could have contributed to the better plant growth and lower mRI in that soil. In conclusion, AGF and BWC have great potential for restoring steel disposal dump areas, and the strategies researched here can contribute to achieving targets for sustainable development. Graphical abstract: Image 1 Highlights: Compost (CSS), ash (AGF) and biochar (BWC) were used in aided phytostabilization. CSS, AGF and BWC improved accumulation of Cd, Cr, Cu, Ni, Zn by L. luteus roots. Ni and Cr showed the highest stability in phytostabilized soil. Arenimonas, Brevundimonas, Gemmatimonas, Variovorax may facilitate soil restoration. L. luteus with AGF or BWC are good for phytomanagement of steel disposal dump areas.